Recent development in high quality drying of fruits and vegetables assisted by ultrasound: A review. (February 2022) - Xu, Baoguo; Sylvain Tiliwa, Essodézam; Yan, Weiqiang; Roknul Azam, S.M.; Wei, Benxi; Zhou, Cunshan; Ma, Haile; Bhandari, Bhesh
Graphical abstract: Highlights: Two modes of ultrasound application in the drying field are presented. Nutrient losses in medium, impedance mismatch and US-temperature competition are the main limitations. Current ultrasonic devices are not efficient for industrial application. US alleviates the degradation of quality properties compared to non-treated samples. Pretreatment may increase processing and labor costs. Abstract: The preservation of agri-products with a high moisture content like fruits and vegetables is challenging. Traditional dehydration techniques (sun drying and hot air drying) were used to limit food degradations and extend shelf life. However, few issues have been raised regarding the long processing time during the dehydration process causing the pronounced oxidation of nutrients and significant energy losses. Recent studies emphasize different process intensification methods, such as ultrasound (US), to rapidly and economically obtain quality dehydrated food to tackle quality deteriorating issues. The current work provides a comprehensive state-of-art of the drying of fruits and vegetables using ultrasound as an improvement technique for quality retention. The review will first provide a global knowledge of ultrasound in the drying field with a special focus on the equipment as well as mechanisms involved when US is used as a pretreatment or simultaneously during various drying processes. Discussion on the efficiency of each ultrasonic device and its potential use in industry is also provided along the way. The second part will cover a critical report and analysis of recent studies highlighting the effects of the two ultrasound application modes in the drying field (pretreatment and combined with the drying process) on the quality of fruits and vegetables. Overall, applying ultrasound to assist the dehydration of fruits and vegetables is a promising way to reduce drying time and obtain nutritious dehydrated products. This non-thermal technology alleviates the oxidation of nutrients, thus offering a favorable perspective to increase the marketability of finished products as public awareness of food quality is surging.